Pendugaan umur simpan kerupuk ale-ale (meretrix meretrix) dengan perbedaan bahan pengemas menggunakan metode accelerated shelf life test (ASLT) model arrhenius: Estimating the shelf-life of ale-ale (meretrix meretrix) crackers with different packaging materials using the accelerated shelf-life test (ASLT) method arrhenius model - Zulfahmi, A Nova; Arianti, Ira; Hastuti, Ningrum Dwi (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
Ale-ale crackers are processed seafood products made from ale-ale shellfish (Meretrix meretrix), which have high nutritional value and economic potential as a value-added snack. However, this product is susceptible to quality degradation due to environmental factors during storage, especially exposure to oxygen and humidity, which can accelerate the degradation process. This study aims to analyze the effect of packaging type on the shelf life of ale-ale crackers using the Accelerated Shelf Life Test (ASLT) method with the Arrhenius model. The research method involves packaging ale-ale crackers in three types of materials, namely polyethene, polypropylene, and aluminium foil, which are stored at controlled temperatures (25°C, 35°C, and 45°C). Observations were carried out periodically for 35 days with test parameters for water content, free fatty acids, and organoleptic tests (texture, aroma and taste). Organoleptic data on texture parameters were analyzed using linear regression models and the Arrhenius equation to predict product shelf life. The research results showed that aluminium foil was the best packaging for maintaining the quality of ale-ale crackers, with increased water content and lower free fatty acids compared to polyethene and polypropylene. Aluminium foil can extend its shelf life up to 63 days at 25°C, while polyethene has the shortest shelf life, only 16 days at the same temperature. The conclusion of this research confirms that the use of packaging materials has a significant effect on the shelf life of ale-ale crackers. Aluminium foil is recommended as the best packaging material to maintain product quality during storage and distribution.